2023
DOI: 10.30604/jika.v8i2.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Therapy to Lower the Tendency to Fear of Missing Out (FoMo)

Abstract: sesudah diberikan mindfulness therapy, jadi ada penurunan yang signifikan dalam fear of missing out (FoMO) setelah diberi terapi mindfulness. Berdasarkan hasil analisis menggunakan Mann-Whitney U Test, nilai Z = -1,481 dan nilai p = 0,139 (p > 0,05), yang berarti tidak ada perbedaan tingkat fear of missing out (FoMO) antara kelompok eksperimen yang diberikan perlakuan mindfulness therapy dengan kelompok kontrol yang tidak. diberikan perlakuan mindfulness therapy. This open access article is under the CC-BY-SA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Several studies confirmed this notion by demonstrating a reduction of FoMO through mindful practice [36]. For instance, Sofia and colleagues [36] suggested that some features of mindful practice (i.e., identifying body reactions and related emotions) contribute to reducing negative affect associated with FoMO with positive implications for individuals' wellbeing [37]. Additionally, past research proved that a mindful attitude is a stable predictor of FoMO.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies confirmed this notion by demonstrating a reduction of FoMO through mindful practice [36]. For instance, Sofia and colleagues [36] suggested that some features of mindful practice (i.e., identifying body reactions and related emotions) contribute to reducing negative affect associated with FoMO with positive implications for individuals' wellbeing [37]. Additionally, past research proved that a mindful attitude is a stable predictor of FoMO.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Specifically, different authors pointed out that a mindful attitude weakens the effect of FoMO, enhancing happiness and wellbeing [34] as well as positive thinking and emotions [35]. Several studies confirmed this notion by demonstrating a reduction of FoMO through mindful practice [36]. For instance, Sofia and colleagues [36] suggested that some features of mindful practice (i.e., identifying body reactions and related emotions) contribute to reducing negative affect associated with FoMO with positive implications for individuals' wellbeing [37].…”
Section: Literature Reviewmentioning
confidence: 97%